(untitled) - Purselle, David C. (Hoboken, N.J., 2003)
The Psychopharmacology Treatment Planner provides all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payors, and state and federal review agencies
Keywords: Mental illness,Psychopharmacology,Bệnh tâm thần,Tâm lý dược học; Chemotherapy,Hóa trị